Purity under pressure - Anderson, Neil T., 1942-; Park, David, 1961- (Eugene, OR Harvest, 1995)
Includes bibliographical references.
Keywords: Chastity / religious -- juvenile literature; Teenagers -- sexual behaviour -- juvenile literature